2002
DOI: 10.1111/j.1651-2227.2002.tb02841.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cholestasis and infantile Gaucher disease: a case report

Abstract: Aim: To report on clinical complications of liver disease occurring during Gaucher disease. Methods: A case of Gaucher disease was revealed by neonatal cholestasis and early onset of portal hypertension. Results: At 7 d of age, a newborn was admitted for cholestasis associated with hepatosplenomegaly and thrombocytopenia. At that time, bone marrow aspirate and liver biopsy did not reveal any engorged cells. The clinical course was marked by early progressive portal hypertension, and the patient died of uncontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…We identified two previous case reports of early onset Gaucher disease with neonatal cholestasis and hepatomegaly and subsequent development of neurological signs consistent with the acute neuronopathic form (type 2) (Barbier et al 2002;Schwartz et al 2009). Details of a liver biopsy performed within the first month of life were available only for one report and, in contrast to our case, did not reveal giant-cell transformation (Barbier et al 2002).…”
Section: Case Discussionmentioning
confidence: 90%
“…We identified two previous case reports of early onset Gaucher disease with neonatal cholestasis and hepatomegaly and subsequent development of neurological signs consistent with the acute neuronopathic form (type 2) (Barbier et al 2002;Schwartz et al 2009). Details of a liver biopsy performed within the first month of life were available only for one report and, in contrast to our case, did not reveal giant-cell transformation (Barbier et al 2002).…”
Section: Case Discussionmentioning
confidence: 90%
“…The fatal digestive bleeding that occurred in P2 may be related to portal hypertension that has been rarely reported in GD. 8,10,11 Failure to thrive observed in our three patients was a precocious and almost constant sign in the French cohort of CGD2. 3 This feature results mainly not only from neurologic feeding difficulties but also from the wasting syndrome that has been proven in patients with neuropathic forms of GD and that we suspected in P1.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cormand et al 7 reported two Spanish cases showing hepatosplenomegaly, ascites and cholestatic jaundice at birth and who died before 4 months of age without any neurological symptoms. Barbier et al 8, and Holleran et al 9 reported each one, a case of CGD2 presenting at birth with cholestatic jaundice, hepatosplenomegaly and thrombocytopenia that persisted isolated until development of neurological signs. The fatal digestive bleeding that occurred in P2 may be related to portal hypertension that has been rarely reported in GD.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient, however, was born to Albanian parents, as was one of the previously reported cases [8] (see below). Direct hyperbilirubinemia is not a common feature of GD although it was present in each of the neonatal case reports we identified [8][9][10][11]. In one case the direct bilirubin was dramatically elevated to 32.0 mg/dL, (with a TSB of 49.5 mg/dL) [10] on day 2 and in our infant it was 16.1 mg/dL (TSB 20.3 mg/dL) on day 5, levels rarely seen in the newborn.…”
Section: Discussionmentioning
confidence: 86%
“…Only 20% of the patients with the type 2 variant have isolated visceral involvement at presentation, with neurological symptoms appearing later [9]. The features of perinatal-lethal GD include hepatomegaly [4], and purpura associated with thrombocytopenia due in part to the splenomegaly that develops.…”
Section: Discussionmentioning
confidence: 99%